2003
DOI: 10.1037/0278-7393.29.4.626
|View full text |Cite
|
Sign up to set email alerts
|

Learning myopia: An adaptive recency effect in category learning.

Abstract: Recency effects (REs) have been well established in memory and probability learning paradigms but have received little attention in category earning research. Extant categorization models predict REs to be unaffected by learning, whereas a functional interpretation of REs, suggested by results in other domains, predicts that people are able to learn sequential dependencies and incorporate this information into their responses. These contrasting predictions were tested in 2 experiments involving a classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 60 publications
6
58
0
Order By: Relevance
“…We assume each forecaster reports the last data point from his private sample. This strategy is consistent with the recency effect whereby people rely on recent experiences in making judgments Yates 2001, Jones andSieck 2003). We call this strategy a report-the-last strategy.…”
Section: Mixed-strategiessupporting
confidence: 51%
“…We assume each forecaster reports the last data point from his private sample. This strategy is consistent with the recency effect whereby people rely on recent experiences in making judgments Yates 2001, Jones andSieck 2003). We call this strategy a report-the-last strategy.…”
Section: Mixed-strategiessupporting
confidence: 51%
“…Data from the preliminary study suggested that participants do not rely on this regularity-discovering and exploiting the regularity would be marked by rarely or never guessing the same category as the correct answer from the previous item. It does remain possible that there is some subtle or implicit learning of sequential structure (see Jones & Sieck, 2003) during the training phase.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, repetition effects from trial n − 1 to trial n must be assessed between proportion-repeated blocks, with prior trial history equated between the two blocks. The analytic procedure based on Jones and Sieck (2003) offered one way to address this issue in Experiment 1, whereas a subtle change to the method was introduced to address this issue in Experiment 2. If differences in PoP as a function of proportion repeated persist, it may be argued that trial-to- trial priming effects are affected by the predictability of trialto-trial contingencies in a context-specific manner.…”
Section: Methodsmentioning
confidence: 99%
“…However, an alternative means of controlling prior trial history was suggested to us by a reviewer, which we also opted to carry out. This procedure derives from the work of Jones and Sieck (2003) and, in the context of the present work, involves looking at priming effects in the following way: We computed mean RTs as a function of whether the target on trial n was a repetition or alternation from trial n − 1 and as a function of whether the target on trial n − 1 was a repetition or alternation from trial n − 2. This yields four trial types (repeat-repeat, repeat-switch, switch-repeat, switchswitch), allowing us to average repeat-repeat and switchrepeat trials together to get a measure of a target repetition from trial n − 1 to trial n, with prior history controlled for, and to average repeat-switch and switch-switch trials together to get a measure of a target switch from trial n − 1 to trial n, with prior trial history controlled for, while maintaining large cell sizes.…”
Section: Response Timesmentioning
confidence: 99%